Improved Vehicle Detection Algorithm in Heavy Traffic for Intelligent Vehicle - Lee, Chung-Hee; Lim, Young-Chul; Kim, Dongyoung; Sohng, Kyu-Ik (Elektronika ir Elektrotechnika, 2014)
Despite significant progress in vehicle detection over the last few decades, vehicle detection performance in heavy traffic is still inadequate. In this paper, we propose a new algorithm for vehicle detection in heavy traffic to improve detection performance. It uses two proposed segmentation methods, namely, the disparity map-based bird’s-eye-view mapping segmentation method and the edge distance weighted conditional random field (CRF)-based segmentation method. Our experimental results show that the proposed algorithm outperforms conventional algorithms. The improvements in performance range from 10.8 % to 20.5 % increase in F-measure. DOI: http://dx.doi.org/10.5755/j01.eee.20.9.3734